Vesicles as a model for controlled (de-) adhesion of cells: a thermodynamic approach - Smith, Ana-Suncana; Seifert, Udo (Soft Matter, 2007)
We review the specific adhesion between ligand-containing vesicles and receptor-functionalized substrates as an established model system used to study the cell recognition process and its control mechanisms. In order to provide better understanding of the underlying physics and to allow for quantitative exploitation of this system, we develop a simple theoretical framework that accounts for the equilibrium state of adhesion and successfully merges the macroscopic and microscopic aspects of the problem. Several mechanisms that are used to control adhesion or induce de-adhesion are studied on the same level of theory. Specifically, the repelling properties of adhesive molecules, the role of repelling molecules, the action of antagonists for a specific binder as well as the influence of an externally applied force are addressed independently within the same formalism.
Keywords: FLUID MEMBRANES; UNBINDING TRANSITIONS; SUPPORTED MEMBRANES; BOUND VESICLES; SURFACE; LIGAND; FORCE; BILAYER; MOLECULES; DYNAMICS